Analysis of KRAS mutations in circulating tumor DNA and colorectal cancer tissue. (4th July 2021) - Liu, Yankui; Li, Longhai; Tian, Yu; Zhu, Xiao; Sun, Aijuan; Sun, Yulong; Qiao, Yan; Qi, Xiaowei; Wang, Tao
ABSTRACT: The mutation status of KRAS is important for anti-EGFR therapy in colorectal cancer (CRC) patients; however, detection of KRAS mutations in circulating tumor DNA (ctDNA) is problematic. We investigated tissue and plasma assays for KRAS mutations in CRC patients. The KRAS status of 407 CRC patients was evaluated using integration of amplification refractory mutation system polymerase chain reaction (PCR), melting curves and wild type DNA blocking (IAMB) in tissue and plasma samples. Disparate cases were re-evaluated by Sanger sequencing of tissue samples. General characteristics and tumor biomarkers including CEA, CA19-9 and CA125 were characterized. The prevalence of KRAS mutations was 40.8% in plasma and 49.1% in tissue. The overall percent agreement, positive percent agreement and negative percent agreement were 82.3, 76.3 and 90.8%, respectively. Older patients and higher TNM stage exhibited increased sensitivity for detecting KRAS mutations in plasma. We found 54.1% of patients with KRAS mutations using parallel analysis of tissue and plasma; only 36.4% of patients were detected by series analysis. We found that plasma based KRAS detection with IAMB technology is an alternative to tissue based KRAS testing. KRAS mutations can be identified more easily when both assays are used together